Test power reduction and test pattern generation for multiple faults using zero suppressed decision diagrams. (2016) - Anita, J.P.; Sudheesh, P.
An algorithm of test pattern generation for multiple faults is proposed using the zero suppressed decision diagrams (ZBDDs). Test pattern generation plays a major role in the design and testing of any chip. The proposed ZBDD is generated from its corresponding binary decision diagram (BDD). A test ZBDD is obtained from the true and faulty ZBDDs and the test patterns are generated from the test ZBDD. The obtained patterns are reordered because the order in which these patterns are used to test the chip is immaterial as far as the faults are concerned but the transitions between the test patterns affect the test power. Hence, the primary objective of the proposed work is the generation of test patterns for a given set of multiple faults. The next objective is to reduce the test power which is the power consumed during testing.